The Effect of Supervision and Quality of Work Life on Organizational Commitment in Work Discipline Moderation at Bank Indonesia Representative Office in North Sumatra Province - M. Agus Hidayat; Kiki Farida Ferine (Yayasan Multidimensi Kreatif, 2024)
Human resources are essentially people who work for an organization as planners, thinkers, and movers to achieve its goals. Human resources (HR) personnel are often highly-skilled individuals who serve as the backbone of an organization. This study aims to see the Influence of Supervision and Quality of Work Life on Organizational Commitment in Work Discipline Moderation at Bank Indonesia Representative Office in North Sumatra Province. The results of this study are as follows: Work Discipline has a positive and significant effect on Organizational Commitment with the original sample value of 0.300 and p values of 0.028. Supervision had a negative and insignificant effect on organizational commitment moderated by Work Discipline with an original sample value of -0.094 and p values of 0.232. The quality of Work Life had a non-significant positive effect on the organization's commitment moderated by Work Discipline with the original sample value of 0.141 and p values of 0.148. The quality of Work Life had a positive and significant effect on Organizational Commitment with the original sample value of 0.278 and p values of 0.033. Supervision had a positive and significant effect on Organizational Commitment with the original sample value of 0.344 and p values of 0.018.